Peran Good Governance dan SPIP dalam Mencegah Tindakan Kecurangan - Aulia Rahma Az zahra; Oryza Tannar (Jurnal Proaksi, 2025)
Main Purpose - The purpose of this study is to analyze the influence of good governance and SPIP on fraud prevention efforts at the Blora Regency Inspectorate.Method - Sampling was conducted using saturated sampling techniques on 33 respondents consisting of auditors and internal supervisors. Data analysis was performed using with SmartPLS 4.0 software.Main Findings - The findings of this study indicate that good governance has a significant effect on fraud prevention, while SPIP has no significant effect. This phenomenon shows that transparency and accountability in governance are more effective in reducing the risk of fraud than the mere existence of a formal control system. The low effectiveness of SPIP is due to its implementation, which is still administrative in nature and lacks monitoring and risk evaluation aspects.Theory and Practical Implications - The theoretical implications of this study reinforce the role of good governance and control systems as tools for value-based fraud prevention.Novelty - This study combines good governance and SPIP as independent variables for fraud prevention in the context of local government oversight institutions.